Estudos de compostos baseado no ligante fenilhidrazonopropanodinitrila para-substituída e seus compostos de coordenação visando sua aplicação em dispositivos ópticos não-lineares - (:unkn) unknown (Universidade Federal de Goiás, 2014)
In this study, the synthesis of five carbonylcyanidephenylhydrazone (ccp), with general formula [RC6H4NHNC(CN)2], where R (= -CH3, -H, -COOH, -CN e -NO2), and their coordination complexes with Ag(I) is presented. Subsequently, these compounds were characterized using spectroscopic methods. The analysis of the compound ccp-H by X Ray diffraction reveals that structurally this compound consists of a nearly linear and planar polymeric form. Data from infrared spectroscopy suggest the formation of hydrogen bonds between the units ccp. In the synthesized Ag(I) coordination compounds, the coordination of each Ag(I) occurs with three ccp units, forming a tridentate ligand-metal coordination with the formation of a three-dimensional structure. In the evaluation of the potential of these compounds to present expressive nonlinear optical properties (NLO), with special attention to the first hyperpolarizability (β), methods from Density Functional Theory (DFT) were employed to describe the structural and electronic characteristics of these compounds, and in the calculation of this parameter. The results show that the incorporation of a group with a strong electron acceptor character, along with the introduction of Ag(I), increases significantly the  values. On the other hand, the results suggest that the CAM-B3LYP functional provides more reliable  values, since the calculations based on this functional reproduced well experimental values of  related to compounds used to calibrate the instrumentation used in these measurements. Based on the estimated  values, it is expected that the studied coordination polymers present promising characteristics for use in photonic devices.
Study of compounds based on binding phenylhydrazonepropanedinitrile para-replaced and its coordination compounds of your aiming for a non-linear optical devices
Keywords: Fenilhidrazonopropanodinitrilas; Ag(I); ONL; DFT; Primeira hiperpolarizabilidade; Phenylhydrazonepropanedinitrile; First hyperpolarizability; CIENCIAS EXATAS E DA TERRA::QUIMICA